Diagnostic pathology gi endoscopic correlation - Yantiss Rhonda K.; Panarelli, Nicole C.; Lamps, Laura W. (Philadelphia Elsevier, 2015)
"Diagnostic Pathology: GI Endoscopic Correlation is designed for the gastrointestinal pathologist, practicing gastroenterologist, and trainees in the field, although it provides useful information to general practitioners in internal medicine and surgical pathology. With nearly 200 diagnoses--all featuring the most recent information and formatted with Amirsys pioneered, bulleted text--this reference provides a comprehensive, atlas-like, overview of endoscopic and microscopic correlates. Thousands of endoscopic, gross, and microscopic images are extensively annotated and serve to highlight clinically and pathologically significant features of disease as well as relevant differential diagnoses. Coupled with a companion eBook, this volume will become a standard reference for all practitioners who participate in the care of patients with gastrointestinal diseases."--Provided by publisher
includes index, bibliographic references
Keywords: Gastrointestinal system -- Diseases -- Atlases; Digestive organs -- Diseases -- Atlases; Endoscopy -- Atlases